2023
DOI: 10.1098/rsif.2023.0004
|View full text |Cite
|
Sign up to set email alerts
|

Native adiponectin plays a role in the adipocyte-mediated conversion of fibroblasts to myofibroblasts

Abstract: Adipocytes regulate tissues through production of adipokines that can act both locally and systemically. Adipocytes also have been found to play a critical role in regulating the healing process. To better understand this role, we developed a three-dimensional human adipocyte spheroid system that has an adipokine profile similar to in vivo adipose tissues. Previously, we found that conditioned medium from these spheroids induces human dermal fibroblast conversion into highly contractile… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Herein we have presented two options for forming spheroids using either a 96-well spheroid plate or agarose micromolds. These are not the only methods for producing spheroids, indeed we have previously used hanging drop method as well [ 10 , 22 , 23 ], but these two options are highly accessible to a large number of labs and are suitable for many experimental needs. The largest trade-off between the two options are whether one needs a large number of spheroids or precise control over the size and variability of spheroids.…”
Section: Anticipated Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein we have presented two options for forming spheroids using either a 96-well spheroid plate or agarose micromolds. These are not the only methods for producing spheroids, indeed we have previously used hanging drop method as well [ 10 , 22 , 23 ], but these two options are highly accessible to a large number of labs and are suitable for many experimental needs. The largest trade-off between the two options are whether one needs a large number of spheroids or precise control over the size and variability of spheroids.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…In addition, spheroid cultures developed large unilocular droplets >20 µm in diameter [ 10 ]. We have since used this method to uncover novel ways in which secreted factors from adipocytes alter fibroblast behaviour [ 22 , 23 ]. In addition, this technique has been adapted by other groups to investigate differences between spheroid and monolayer phenotypes in different species and cell types [ 24 ] and to incorporate immune cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous investigation reported that individuals with an elevated adiponectin-to-leptin ratio demonstrated poorer survival outcomes compared to those with severe IPF and a reduced adiponectin-to-leptin ratio [ 24 ]. Nonetheless, experimental research has demonstrated that adiponectin can suppress the expression of alpha-smooth muscle actin (α-SMA), type I collagen, and pro-inflammatory cytokines [ 25 26 ]. Adiponectin has been proposed as a potential therapeutic agent for fibrosis-associated pathologies, its antifibrotic properties potentially mediated through the inhibition of the nuclear factor-kappa B (NF-κB) signaling pathway [ 27 ].…”
Section: Discussionmentioning
confidence: 99%